2022
DOI: 10.1038/s41598-022-17465-9
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of the bridging cerebral cortical veins in childhood hydrocephalus suggests a malfunction of venous impedance pumping

Abstract: Dogs with a naturally occurring form of hydrocephalus have an elevated transmural venous pressure leading to cortical vein dilatation. The purpose of this study is to discover if there is vein dilatation in childhood hydrocephalus and to estimate the pressure required to maintain any enlargement found. Children with hydrocephalus between the ages of 4 and 15 years were compared with a control group. Magnetic resonance venography (MRV) and flow quantification were performed. The arterial inflow, sagittal sinus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In a previous modelling study, the elastic modulus in humans was estimated to be 0.163 MPa, the vein thickness was 0.044 mm and the resting state radius of the veins in the review was 1.55 mm [36]. As these values are not expected to change during changes in the transmural pressure, it can be seen that the change in the vessel area compared to the stress free state will vary with the transmural pressure.…”
Section: Vessel Responses To Transmural Pressure Variationsmentioning
confidence: 94%
“…In a previous modelling study, the elastic modulus in humans was estimated to be 0.163 MPa, the vein thickness was 0.044 mm and the resting state radius of the veins in the review was 1.55 mm [36]. As these values are not expected to change during changes in the transmural pressure, it can be seen that the change in the vessel area compared to the stress free state will vary with the transmural pressure.…”
Section: Vessel Responses To Transmural Pressure Variationsmentioning
confidence: 94%
“…In human subjects, the bridging veins show a mean diameter of 2.04 mm under normal intracranial pressure and increase to 2.65 mm under an increased ICP [38], a 69% increase in cross-sectional area. Finally, in children with hydrocephalus, the superficial territory cortical veins were 22% larger than the controls, with modelling suggesting a significant increase in the superficial vein transmural pressure in childhood hydrocephalus estimated to be approximately 4 mmHg [39]. In MS, the bridging vein dilatation suggested an increase in the transmural pressure estimated to be approximately 6.5 mmHg in the superficial cortical veins overall and those with significant fatigue had greater dilatation in the territory draining the cortical grey matter than those without fatigue [19].…”
Section: Bridging Vein Dilatationmentioning
confidence: 94%
“…In MS, the bridging vein dilatation suggested an increase in the transmural pressure estimated to be approximately 6.5 mmHg in the superficial cortical veins overall and those with significant fatigue had greater dilatation in the territory draining the cortical grey matter than those without fatigue [19]. We have previously suggested an impedance mismatch alters the blood flow through the terminal cortical vein segments increasing their pressure with either loss or reversal of the hydraulic engineering effect known as impedance pumping [39]. It is likely that the cortical vein pressure feeds back into the parenchymal venules.…”
Section: Bridging Vein Dilatationmentioning
confidence: 99%
“…Recently, the dilatation of the superficial cortical veins draining the brain has been noted in children with hydrocephalus [7]. Modelling suggested that dilatation could only be brought about via an increase in the venous transmural pressure of approximately 4 mmHg [7]. It was suggested that a change in impedance pumping could account for this finding [7].…”
Section: Introductionmentioning
confidence: 99%
“…Modelling suggested that dilatation could only be brought about via an increase in the venous transmural pressure of approximately 4 mmHg [7]. It was suggested that a change in impedance pumping could account for this finding [7]. It has now been recognised that this same phenomenon could produce an increase in venous pressure within the cord in syringomyelia.…”
Section: Introductionmentioning
confidence: 99%